2015
DOI: 10.1080/15384047.2015.1113356
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of 6,892 colorectal cancer samples suggests different possible treatment options specific to metastatic sites

Abstract: Metastatic colorectal cancer (mCRC) carries a poor prognosis with an overall 5-year survival of 13.1%. Therapies guided by tumor profiling have suggested benefit in advanced cancer. We used a multiplatform molecular profiling (MP) approach to identify key molecular changes that may provide therapeutic options not typically considered in mCRC. We evaluated 6892 mCRC referred to Caris Life Sciences by MP including sequencing (Sanger/NGS), immunohistochemistry (IHC) and in-situ hybridization (ISH). mCRC metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
61
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 61 publications
13
61
5
Order By: Relevance
“…In the context of brain metastases from GI primary malignancies being a rare event, the current study represents the largest cohort, to our knowledge, of patients with GI cancer with paired tissue from a brain metastasis and prior site of disease examined for HER2 status by FISH and IHC. Several prior studies have examined HER2 status in primary GI tumors or metastatic sites of disease and have variably suggested that HER2+ GI cancers may have a predisposition for spread to the brain, but very few patients included in these studies have had paired prior tissue and brain metastasis tissue available, which has limited the ability to see the dynamics of HER2 status over the course of disease evolution .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of brain metastases from GI primary malignancies being a rare event, the current study represents the largest cohort, to our knowledge, of patients with GI cancer with paired tissue from a brain metastasis and prior site of disease examined for HER2 status by FISH and IHC. Several prior studies have examined HER2 status in primary GI tumors or metastatic sites of disease and have variably suggested that HER2+ GI cancers may have a predisposition for spread to the brain, but very few patients included in these studies have had paired prior tissue and brain metastasis tissue available, which has limited the ability to see the dynamics of HER2 status over the course of disease evolution .…”
Section: Discussionmentioning
confidence: 99%
“…As in breast cancer, prior studies in GI cancer have suggested HER2+ primary malignancies have a propensity for central nervous system (CNS) metastases. However, most of these studies have focused on GEJ AC, with pathologic evaluation typically performed on primary tumor lesions with infrequent availability of paired intracranial metastatic tissue . The current study examines the HER2 status of patients with a variety of GI primary malignancies, all of whom have brain metastases with tissue available and the majority of whom also have tissue from a prior site of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of ERBB2 amplification and sequence mutations in colorectal cancer (CRC) suggest that HER2 is a therapy target in this disease, in addition to being a mechanism of resistance to epidermal growth factor receptor (EGFR)‐targeted therapies such as cetuximab and panitumumab . Similarly, reports of high‐level ERBB3 amplification being a negative prognostic factor within the context of CRC suggest that HER3 may also be a target in this tumor type .…”
Section: Introductionmentioning
confidence: 99%
“…Mutation profiles of primary tumor versus the metastatic lesion locoregional lymphatic metastasis versus distant metastasis need to be carefully assessed, as often the profiles are not identical. [57][58][59] Similarly, you cannot assume that multiple tumors in the same patient and of the same tumor type will possess the same mutation profile. Second, what criteria are appropriate for defining a positive test result that will then impact clinical management?…”
Section: Technical Issues To Consider For Implementing Somatic Mutatimentioning
confidence: 99%